La gestione strategica delle Risorse Umane: implicazioni per il management sanitario da una rassegna sistematica della letteratura - Dello Russo, S. (2016)
The present work reports on a systematic review of the literature about human resource (HR) management and their strategic contribution in the healthcare sector. Through the analysis of 57 articles, we have examined the main theoretical approaches and models adopted by researchers, the samples, the specific HR practices and their relation with several criteria of organizational efficacy. This analysis has led to understanding the evolution of the research in this field and the identification of important directions for future research and organizational practice.